2024
DOI: 10.1007/s11695-024-07154-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dynamic Measures in Intraoperative Goal-Directed Fluid Therapy of Patients with Morbid Obesity Undergoing Laparoscopic Sleeve Gastrectomy

Gökhan Urhan,
İsmail Demirel,
Ahmet Deniz
et al.

Abstract: Introduction Obesity increases the risk of morbidity and mortality during surgical procedures. Goal-directed fluid therapy (GDFT) is a new concept for perioperative fluid management that has been shown to improve patient prognosis. This study aimed to investigate the role of the Pleth Variability Index (PVI), systolic pressure variation (SPV), and pulse pressure variation (PPV) in maintaining tissue perfusion and renal function during GDFT management in patients undergoing laparoscopic sleeve gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Among all other dynamic hemodynamic parameters, PVi is by far the less invasive and more convenient in terms of cost [33]. In addition, several veterinary and human studies have demonstrated its accuracy compared to invasive methods [15].…”
Section: Discussionmentioning
confidence: 99%
“…Among all other dynamic hemodynamic parameters, PVi is by far the less invasive and more convenient in terms of cost [33]. In addition, several veterinary and human studies have demonstrated its accuracy compared to invasive methods [15].…”
Section: Discussionmentioning
confidence: 99%